Механізм введення в експлуатацію самовільно побудованих індивідуальних житлових об’єктів - Титок, В. В. (Ways to Improve Construction Efficiency, 2014)
The paper defined the order of procedures required by law to carry out the construction of individual houses, as well as actions of the owner of the object unauthorized construction, which wants to legalize construction.